Action and resistance of monoclonal CD20 antibodies therapy in B-cell Non-Hodgkin Lymphomas. Issue 8 (September 2015) - Pérez-Callejo, D.; González-Rincón, J.; Sánchez, A.; Provencio, M.; Sánchez-Beato, M.
Abstract : Highlights: Anti-CD20 mAbs combined with chemotherapy have become the standard treatment of Non-Hodgkin Lymphomas (NHL). Mechanisms of action of this anti-CD20 mAbs in vivo are not fully understood. Binding of rituximab to CD20 is not sufficient to heal every patient with a Non-Hodgkin Lymphoma. We review the mechanisms of action and resistance of rituximab, and the efforts needed to overcome it. We also focus on new drugs targeting pathways implicated in resistance to anti-CD20 mAbs. Abstract: Anti-CD20 monoclonal antibodies (mAbs) have improved patient's survival with Non-Hodgkin Lymphoma, when combined with chemotherapy. Several mechanisms of action have been reported, including antibody-dependent cellular cytotoxicity, complement-dependent cytotoxicity and induction of apoptosis. Despite the large amount of studies and published data, the role each mechanism played in vivo is not fully understood. Furthermore, the reason why a significant percentage of patients are refractory or resistant remains unknown. Several activated intracellular signaling pathways have been implicated in the mechanisms of resistance of rituximab. In the present manuscript, we review those mechanisms and new anti-CD20 mAbs, as well as the efforts being accomplished to overcome it, focusing on new drugs targeting pathways implicated in resistance to rituximab.